Methods of Using Literatural Materials in Primary School Lessons - Qizi, Akbarova Mohinur Nizomiddin (European Journal of Life Safety and Stability (2660-9630), 2021)
This article discusses how to organize lessons in native language classes using the materials of the PIRLS international assessment program. The PIRLS international program aims to provide students with a broader understanding of the ability to read and comprehend text, to come up with new ideas, ideas about other cultures and different countries. Assessment of student achievement is based on objective tests, not on all students, but on students selected as representatives of this layer.